PERLUASAN WEWENANG MAHKAMAH KONSTITUSI SEBAGAI PENGAWAL KONSTITUSI - Yenny, Oktavani (Faculty of Law, Tanjungpura University, 2020)
Becoming one of the materials inside the fifth amendment of Undang-Undang Dasar Negara Republik Indonesia 1945 (The 1945 Constitution of Republic Indonesia), Constitutional Court authority now has become one of the essential concerns given that the function as